THE WISDOM AND EDUCATIONAL VALUES OF THE VERSES MUHKAMAT AND MUTASYABIHAT IN THE QUR’AN (International Conference on Social and Islamic Studies, 2021)
This study aims to analyze the wisdom and educational values of the verses of Muhkamat and Mutasyabihat in the Qur'an. Al-Quran is a guide, a resource and reference for all people. All things related to Al-Quran is deemed noble and commendable. Therefore, the study of AlQuran still continues because it contains very broad and deep , including problems muhkam and mutasyabih. “Ayat muhkam” is the subject of the Qur'an, and there are some “ayat mutasyabih” whose meaning is restored to “ayat muhkamat”. Takwil to “ayat mutashabihat” done not only by khalaf generation, but the generation of the Salaf (the first three centuries of Hijra) also did the same thing. The method used in this research is library research where the writer tries to find, compile and analyze various information through various related sources. The Qur'an has functions as a bayan (explanatory) and hudan (guidance) which contains an explicit verse or muhkam. Besides, it also has functions as the greatest miracle and literary book in human history which contains an implicit verse or mutasyabih that will never end to be studied and researched. Muhkamat and mutasyabihat verses are two complementary things in the Qur'an. There is an immeasurable wisdom and educational value for both. Therefore, in learning and understanding both is as well as learning the wisdom of decreasing the Qur'an itself.